A Comparative Qualitative Analysis Of Some Varieties Of Mulberry (Morus Spp.) (Applied Biological Research, 2020)
The sustainability of sericulture industry depends on the growth of silkworm which, in turn, depends  on the leaf quality of mulberry on which the silkworms feed. To meet the feed demands of silkworm,  it is essential to evolve high yielding mulberry varieties possessing high quality nutritive leaves as  well as the ability to grow under varied agro-climatic conditions throughout the year. Silkworm is a  monophagous insect, therefore the carbohydrate and protein contents in mulberry foliage play vital role in quality silk production. Young silkworms require succulent leaves for easy ingestion, while  late-age silkworms can feed on mature leaves as they have the strength to cut and ingest the hard  leaves which usually possess less proteins and water (Srichaikul et al., 2011). The availability of  moisture content in leaves enhances the feeding efficiency of silkworm larvae which, in turn,
Keywords: Comparative; Qualitative Analysis; Varieties